Ten Tricky Questions about Narrative Inquiry in Language Teaching and Learning Research: And What the Answers Mean for Qualitative and Quantitative Research - Barkhuizen, Gary (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This article addresses ten ‘tricky’ questions related to narrative inquiry in the field of language teaching and learning research. The questions come from the author’s experiences of presenting lectures and seminars on narrative inquiry in many different contexts. The questions deal with issues to do specifically with narrative inquiry methods as well as with broader issues related to narrative research approaches. Where applicable, reference is made to the implications the answers have for both qualitative and quantitative research. The article starts with a brief overview of what narrative inquiry is in the context of language teaching and learning research.